LUSI Burst: Addressing Toxic Mud Flows in Indonesia Through Disaster Recovery and Mitigation Strategies - Nalarsih, Retno Tri (Revenue Journal: Management and Entrepreneurship, 2024)
A major volcanic eruption in May 2006 near a gas drilling site in Sidoarjo, Indonesia, continued to emit toxic substances, including the dangerous chemical phenol. Phenols, which are found in oil and gas, pharmaceuticals, paint, and electronics, can cause human skin, eye, and mucous membrane irritation if exposed. The impact of the Lapindo mudflow has been detrimental to the economy, society, and ecology, including damage to agricultural land, disruption of livelihoods, and business closures. This research aims to identify effective disaster recovery and mitigation strategies in dealing with toxic mudflows. Authorities have planned to divert mud into the Porong River, convert the affected area into a tourist attraction, and use control pumps to deal with flooding. However, the collapse of the mud embankment caused public concern about flooding and loss of life. This study uses snowball sampling and phenomenology methods, focusing on residents around the Lapindo embankment area in Gempolsari Village. Data was collected through interviews, observation, and photo documentation. The research results show the importance of mitigation strategies that involve village halls to provide information and build residents' confidence in facing disasters. It is hoped that these findings will provide insights for the development of more effective disaster mitigation systems.